Blood Revenge in Civil War: Proof of Concept. (1st January 2023) - Souleimanov, Emil Aslan; Siroky, David S.; Colombo, Roberto
Abstract: As an embedded sociocultural code, blood revenge is present in many societies where civil wars occur. Whereas evidence from other social sciences attests to its enduring global significance, security studies scholarship has largely neglected the custom of blood revenge. This article is the first to investigate its relevance for understanding the inception, dynamics, and aftermath of armed conflicts, and to present a comprehensive account of how blood revenge may shape civil wars. Drawing upon multidisciplinary scholarship, cross-case qualitative evidence, and a newly compiled dataset, this proof-of-concept article illustrates how blood revenge influences key dynamics in civil wars—specifically, the processes of violent mobilization, target selection, recruitment, defection, and disengagement. Setting the stage for further inquiries into the causes, mechanisms, and consequences of blood revenge in civil war, this conceptual article suggests why and how this sociocultural code continues to influence civil wars across the world.